Internet marketing for entrepreneurs using Web 2.0 strategies for success - Payton, Susan; Safari eBooks (New York : Business Expert Press, 2009)
"This book is your introduction to Marketing 2.0. It shows you how to leverage new media tools like Facebook, Twitter, blogs and the New Media Press Release to grow your business and your followers, as well as how to participate in meaningful conversations with past, present and future customers. The book will also identify strategies you can implement immediately to grow awareness of your brand online"--Resource description page.
Introduction -- Chapter 1: making sense of marketing 2.0 -- Chapter 2: getting social online -- Chapter 3: blogging for business -- Chapter 4: hot off the (virtual) presses! -- Chapter 5: easy e-mailing -- Chapter 6: bringing it all together -- Glossary -- Appendix A: marketing plan -- Appendix B: press release example -- Appendix C: press release distribution sites -- Appendix D: more information on press releases -- Appendix E: e-mail sample -- Appendix F: marketing plan outline -- Appendix G: blog posts by social media experts -- Index.
Description based on resource description page (viewed June 30, 2010).
Includes index.
Keywords: Internet marketing; Online social networks; Small business marketing; Electronic books